The Broken "Ring of Fire": A New Radiological Sign as Predictor of Syndesmosis Injury?. Issue 3 (20th March 2017) - Calder, James; Mitchell, Adam; Lomax, Adam; Ballal, Moez S.; Grice, John; van Dijk, Niek; Lee, Justin
Background: Subcircumferential periosteal edema above the ankle joint is frequently present on magnetic resonance imaging (MRI) with syndesmosis injuries but has not been previously reported. Fluid height within the interosseous membrane also has not previously been shown to be associated with syndesmosis injury severity. Purpose: To investigate whether a new sign on MRI and measurement of the length of fluid within the interosseous membrane above the ankle may be used to enable identification of a syndesmosis injury and allow differentiation from lateral ligament injury. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Three groups of patients (those with an isolated syndesmosis injury [SI group], isolated lateral ligament injury [LLI group], and no injury [NI group]) who had an ankle MRI for another reason were identified from a patient notes database and the MRI scans retrieved. The scans were anonymized and independently assessed by 8 clinicians (surgeons and radiologists) who were blinded to the diagnosis. The maximum length of fluid above the ankle within the intraosseous membrane was measured for each patient. The presence or absence of distal anterior, lateral, and posterior tibial periosteal edema was recorded (broken "ring of fire"). Results: Measurement of the length of fluid above the ankle had excellent intraobserver reliability (intraclass correlation coefficient, 0.97; 95% CI, 0.93-0.99) but poor interobserver reliability. Fluid extended higher in both the LLI group ( P = .0043) and SI group ( P = .0058) than the NI group, but there was no significant difference between the LLI and SI groups ( P = .3735), indicating that this measurement cannot differentiate between the injuries. The presence of the broken "ring of fire" around the distal tibia was significantly more frequent in the SI group when compared with both LLI and NI groups ( P < .00001). The sensitivity of this sign is 49%, but when present, this sign has a 98% specificity for syndesmosis injury. Conclusion: The presence of tibial subcircumferential periosteal edema 4 to 6 cm above the ankle joint (the "ring of fire") is highly suggestive of a syndesmosis injury. This new radiological sign can assist with early identification of such injuries. The measurement of height of fluid above the ankle within the interosseous membrane is variable and cannot differentiate severe ankle sprains from high ankle sprains involving the syndesmosis.